Inquiry Training with WhatsApp for Learning in Vocational Schools - I Gede Budi Mahendra; Jocke Jonathan Rapar; Viverdy Memah; Billy Killis (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
Learning at vocational schools aims to prepare the younger generation for work or entrepreneurship. However, in Indonesia, vocational school graduates are the highest contributor to unemployment, namely 9.6%. To increase the competitiveness of graduates, vocational schools must improve the quality of education and vocational skills, especially scientific and mathematical process skills. The objective of this research is to assess the influence of incorporating the WhatsApp-assisted inquiry training on the science process skills and mathematical representation abilities of vocational school students enrolled in the electricity skills program. The study was carried out as a quasi-experiment employing a non-equivalent control group design. A saturated sample of 85 respondents from three classes, including one experimental class and two control classes, was utilized. Prior to the intervention, a pretest was administered. The experimental class received the inquiry training with WhatsApp, while the control class 1 received the inquiry training, and the control class 2 received the direct instruction. The findings of the study indicate that the inquiry training with WhatsApp yields a positive impact and is more effective in enhancing the science process skills and mathematical representation abilities of vocational school students in comparison to the inquiry training model and the direct instruction model, achieving an mean score of 84.16 and an N-Gain score of 0.72 in the high category.